If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 = 64 + 2x Reorder the terms: 9 + 7x = 64 + 2x Solving 9 + 7x = 64 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + 7x + -2x = 64 + 2x + -2x Combine like terms: 7x + -2x = 5x 9 + 5x = 64 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + 5x = 64 + 0 9 + 5x = 64 Add '-9' to each side of the equation. 9 + -9 + 5x = 64 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 64 + -9 5x = 64 + -9 Combine like terms: 64 + -9 = 55 5x = 55 Divide each side by '5'. x = 11 Simplifying x = 11
| 6x^2+3x+1=0 | | 5x-11=3x+7 | | 9x+=152 | | 7x-y=19 | | 0.04x(x-12)+0.06x=1.52 | | x-92=10 | | b-10=8 | | x/7=9.2 | | 3x+4-x=2x+1 | | 5(x-3)+7(2-x)-4(2x+7)-3x+2=11-8x-56+4x-(-6-5x)+8-2x | | 6=15+x | | -8=x-7 | | c-9=3 | | -2x+3y=-19 | | z+4=-13 | | 4(2)+17=27 | | 4x^3-10x^2-6x+15=0 | | 14=x+9 | | x-49=-56 | | a+8=-4 | | 4=-(2x+3) | | 3(9-8-4x)+8(3x+4)=11 | | -18=x-35 | | y+7=63 | | 3x=8x+15 | | 14x^2+21x= | | n-2=7 | | 7y-35=2y | | .12(12)+.02x=.04(12+x) | | 3(5)= | | 7x=2x+36 | | 0=x^2-2x-20 |